Soil and Water Resource Management for Sustainable Agriculture: Exploring Integrated Approaches for Climate-Smart Farming - Dani Lukman Hakim; Noorhani Dyani Laksmi; Lovi Sandra (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Climate change poses significant challenges to global agriculture, impacting soil and water resources. The increasing variability in rainfall patterns, droughts, and soil degradation necessitates sustainable management practices. Effective management of these resources is critical to ensuring long-term agricultural productivity and food security, especially in the face of climate change. Purpose. This study aims to explore integrated approaches for managing soil and water resources within the context of climate-smart farming. It investigates how adopting these practices can enhance resilience to climate variability, improve soil health, and optimize water use efficiency in agriculture. Method. A mixed-methods approach was employed, combining quantitative soil and water data analysis with qualitative interviews from farmers, agricultural experts, and policymakers. The study was conducted in regions impacted by climate change, with a focus on sustainable agriculture practices like rainwater harvesting, soil conservation, and water-efficient irrigation techniques. Results. Findings indicate that integrated resource management strategies, including conservation tillage, agroforestry, and precision irrigation, significantly improved soil fertility, reduced water use, and enhanced crop yields. The adoption of climate-smart practices also led to increased resilience against extreme weather events. Conclusion. The study concludes that integrated approaches to soil and water resource management are essential for sustainable agriculture in the era of climate change. These practices not only ensure environmental sustainability but also contribute to food security and farmer livelihoods.